A biomimetic chiral-driven ionic gate constructed by pillar[6]arene-based host–guest systems - Yue Sun (Nature Portfolio, 2018)
Uptake and release of glucose is regulated by glucose-sensitive ion channels, but complexity of the system impedes investigation of the gating behavior under physiological conditions. Here the authors use a pillararene based artificial ion channel to mimic and investigate chirality driven switching of a glucose ion channel.